National debt (London Her Majesty's Stationery Office, 1960)
This return gives particulars of the changes in the National debt in the year 1938-39, 1947-48, and 1959-60 and of the issues made of the service of the debt in the same periods.
Bound over five years 1959 - 64
osc 22/6/17
Loans
Keywords: Debt, public; United Kingdom